Improving Pandemic Integrated Care Using Digital Technology for Health Care Organisation: A Qualitative Study - Eryando, Tris; Afrizal, Sandra Hakiem (Jurnal Kesehatan Masyarakat, 2024)
Study for exploring the pandemic integrated care through the implementation of health information system using digital technology is very limited. Thus, the research findings provide genuine information regarding the system integration assessment for the regulators and provide an integrated COVID-19 as the system design sample as a robust solution. The authors evaluated the implementation of the current COVID-19 information system to explore and describe the barriers and challenges from the perspective of the COVID-19 Task Force Team of the South Tangerang District, Indonesia and to propose an effective design of COVID-19 functional integrated system. A qualitative form of research was conducted in the South Tangerang District during May 2020. The area was selected as it was the only red zone in Banten Province during the Coronavirus pandemic in Indonesia. In-depth interviews were applied to explore the barriers during the implementation of functional integrated system for the COVID-19 pandemic. Three (3) themes of barriers were identified as involved in functional integration through the implementation of the COVID-19 information system, namely individual behavior, data governance in the organisation, and communication and networks.